Students’ Reasoning in Mathematics Learning: How to Solve Problem of Ethnomathematics Based on Personality - Putri, Kharisma Dwisinta; Ekawati, Rooselyna; Shodikin, Ali (Journal of the Indonesian Mathematics Education Society, 2024)
Reasoning relates to the extent which students can think about the flow of problem solving. Combined in ethnomathematics so that students know more about mathematical practice through local culture. There was a statement of study say that personality types which reflect differences in a person's way of thinking. This study aims to analyze students' reasoning through ethnomathematics based on personality. The subject taken from grade eight junior high school students were selected, each of whom include in masculine, neutral, and feminist category from personality. Research method applies a qualitative method. Sampling technique applies cluster random sampling. Data collection technique applies documentation, observation, and test method. The result to all of the category that were masculine, neutral, and feminist had same quality enough in perform calculations based on certain rules or formulas, quality good in make conjecture, and quality less in checks the validity of an argument. However they was not duplicate answer. For other researchers may continue similar research by considering another indicator of students’ reasoning to comparison whether there are different result or be better than this research.